Teachers’ Perceptions of Deep Learning Pedagogy in Indonesian Primary Schools: Evidence from the Wahidin Sudiro Husodo Cluster - Elinda Rizkasari; Ema Butsi Prihatsari; Anggit Grahito Wicaksono; Jumanto Jumanto; Hanifah Hanifah (LJPI UI Bunga Bangsa Cirebon, 2026)
Deep learning pedagogy has recently been promoted as a strategic response to the evolving demands of Indonesian basic education under the Merdeka Curriculum, which emphasizes student-centered learning, meaningful projects, and the cultivation of 21st-century competencies. Objective: This study investigates primary school teachers’ perceptions of deep learning pedagogy within the Wahidin Sudiro Husodo Cluster, Jumapolo Subdistrict, Karanganyar Regency. Novelty: Implications for developing a teacher training model and future research directions are discussed. Methods: Using a descriptive survey design, data were collected from 30 teachers across eight schools through a structured questionnaire (Likert scale) and complemented by short interviews and documentation review. The survey assessed three major dimensions: conceptual understanding of deep learning, classroom enactment, and school-level readiness for implementation. Results: Findings show that teachers’ conceptual understanding reached a “good” level (M = 3.65 on a 1–4 scale), while classroom enactment was “fairly good” (M = 3.40) and readiness for implementation remained “moderate” (M = 3.25). Qualitative evidence indicates that teachers commonly interpret deep learning as meaningful learning and higher-order thinking, yet some still conflate it with general active learning. Teachers reported constraints related to time allocation, learning media availability, class size, and limited technical training, despite acknowledging the relevance of project-based and problem-based learning for deep learning pedagogy. Conclusions: The study concludes that deep learning pedagogy is viewed positively but requires systemic support through structured professional development, school leadership facilitation, and practical guidance for authentic assessment and reflective learning routines.